The Future of Water for Food - Mohtar, Rabi H.; Fares, Ali (Frontiers in Sustainable Food Systems, 2022)
Globally, water is a bottleneck to food security and, as such, a new approach for water for food is needed. Food insecurity is knocking at every nation's door, including those of the most developed. Moreover, the disruptions in food supply chains that result from continued reliance on a business-as-usual approach of traditional, non-sustainable food and agricultural systems make food insecurity even more vividly present. This article explores the current relationship between food production and water resources. It attempts to better understand how we might reduce the inter-dependencies between food and fresh water by exploring new and alternative sources of water, including improving the efficiencies of green and recycled water.